PENGARUH DESENTRALISASI FISKAL TERHADAP KEMISKINAN DI KABUPATEN BENGKALIS PROVINSI RIAU (PERIODE 2006-2017) - Rudi Tambunan; Dahlan Tampubolon; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted in the Regency of Bengkalis, Riau Province. This research aims to know the influence of fiscal decentralization against poverty in Bengkalis Regency, Riau Province. In this data that become the population and sample the entire object reports annually from the Regency of Bengkalis. This research data using data time seriesdata which consists of 12 years starting from 2006 up to the year 2017. Sampling technique is used is to do an observation that is by collecting data and observe directly the object of research from data obtained in the Bengkalis Regency Government Office, Riau Province. Types of data used in this research is secondary data. Methods of analysis used in this research is quantitative descriptive method, analysis of partially and simultaneous (multiple linear regression analysis with the help of the program SPSS version 21.0). From the results of research that has been conducted, simultaneous regression test (F Test) shows that the whole of the free variables examined have significant influence towards the level of poverty in the Province. Partial regression test (test t) indicates that the variable revenue sharing fund without tax have negative influence and significant variable against poverty. While the variable revenue sharing fund with tax, special allocation fund, General allocation fundhave negative and insignificant against the poverty variables. The magnitude of the influence that caused (R2 ) by four of these variables together against variables bound of 85.5%, while the rest of 14.5% is affected by other variables which are not examined in this study.Keywords : Fiscal decentralization, revenue sharing fund with tax, revenue sharing fund without tax, special allocation fund, General allocation fundand poverty.